Social Policy in the United States : Future Possibilities in Historical Perspective - Skocpol, Theda (Book collections on Project MUSE., 2011)
Readers will be surprised at many of the findings and arguments of this volume. Skocpol dispels the myth that Americans are inherently hostile to governmental social spending. When universal social programs jointly benefit the middle class and the poor, she shows, Americans since the nineteenth century have been willing to pay taxes for them and happy to partake of the security they provide. Insights from the past also illuminate why ideological attacks against "bureaucratic meddling" by the federal government repeatedly prove so potent in U.S. politics. Skocpol suggests why President Clinton's proposals for comprehensive health care reforms were so quickly attacked, even though Americans agree that the health financing system is in crisis and support universal insurance coverage.